2021
DOI: 10.2196/30833
|View full text |Cite
|
Sign up to set email alerts
|

Shift in Social Media App Usage During COVID-19 Lockdown and Clinical Anxiety Symptoms: Machine Learning–Based Ecological Momentary Assessment Study

Abstract: Background Anxiety symptoms during public health crises are associated with adverse psychiatric outcomes and impaired health decision-making. The interaction between real-time social media use patterns and clinical anxiety during infectious disease outbreaks is underexplored. Objective We aimed to evaluate the usage pattern of 2 types of social media apps (communication and social networking) among patients in outpatient psychiatric treatment during the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A pandemic report found that Spain was the top third European country for increases in social network activity during the beginning of the COVID-19 pandemic [ 7 ], and our data validates these increases. Early reports found these social media increases as being harmful to mental and physical health [ 6 , 31 , 32 , 34 ], although with recent data and our data suggesting there were several benefits to these increases such as social support, it is possible that without initial qualitative data to assess the reasons and implications of the social media use increases, the negative results originally found were confounded by experiences of stress, anxiety, depression, helplessness, and loneliness that were experienced by so many during the pandemic. Thus, while in general, overuse of social media can potentially be harmful and cause lower mental health, our data provides evidence that in a time of crisis and isolation, social media use can be leveraged for health benefits and needed social support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pandemic report found that Spain was the top third European country for increases in social network activity during the beginning of the COVID-19 pandemic [ 7 ], and our data validates these increases. Early reports found these social media increases as being harmful to mental and physical health [ 6 , 31 , 32 , 34 ], although with recent data and our data suggesting there were several benefits to these increases such as social support, it is possible that without initial qualitative data to assess the reasons and implications of the social media use increases, the negative results originally found were confounded by experiences of stress, anxiety, depression, helplessness, and loneliness that were experienced by so many during the pandemic. Thus, while in general, overuse of social media can potentially be harmful and cause lower mental health, our data provides evidence that in a time of crisis and isolation, social media use can be leveraged for health benefits and needed social support.…”
Section: Discussionmentioning
confidence: 99%
“…Further, those who reported greater well-being also reported spending less time on social networking sites, and those who engaged in more use of these sites were less happy than those who did so modestly, and had lower general and social well-being [ 6 ]. Contrarily, a study of psychiatric outpatients in Spain found that those who used social media more frequently during the lockdown period engaged in more physical activity [ 33 ], and that those who reported higher anxiety symptoms were more active in social networking apps (e.g., Facebook, Instagram, Twitter) and less active in communication apps (e.g., WhatsApp, telegram) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…And in the context of the ever-increasing digitization of healthcare and everyday life, the “behavioral” data seem almost limitless. For example, in psychiatry, the concept has been used to describe how home visits—measured using a visit detection system—may be a biomarker of geriatric depression (Schutz et al, 2021), how the frequency of social media app use among outpatients may be a biomarker of a generalized anxiety disorder (Ryu et al, 2021), and how skipping the use of a breathalyzer, which is connected to a smartphone by an app, may be a biomarker for assessing alcohol use disorder (Zetterström et al, 2019).…”
Section: Digital Biomarkers: Redefining a Biological Conceptmentioning
confidence: 99%
“…Fauziah et al [12] developed two machine language algorithms, the random forest and xgboost in order to detect the anxiety feeling during the pandemic, where the author used 4862 records from a dataset that was collected from YouTube comments. Moreover, [13] used the Machine Learning for detecting the patients' anxiety during the Covid-19 pandemic by using data from two different types of social media apps namely a communication app as well as a social networking app. On the other hand, [14] used Facebook's dataset in order to predict the spreading of new cases of Covid-19.…”
Section: Sentiment Analysis Based On Social Media Posts During Covid-19mentioning
confidence: 99%